Motives and Enjoyment of Watching Dashcam Videos on Social Media: A Phenomenological Study on Generation Z in Semarang - Taruna Budiono; Ratna Asih Setyaningrum; Arfika Pertiwi Putri (CHANNEL: Jurnal Komunikasi, 2026)
This study aims to examine the psychological motives and gratifications that underlie Generation Z’s consumption of user-generated dashcam videos on social media, using the Uses and Gratifications Theory as the guiding framework. A qualitative descriptive design with a phenomenological approach was employed to explore participants lived media experiences. Nine Generation Z individuals aged 18–21 years were selected as digital natives. Data were collected through in-depth interviews and analyzed using thematic analysis to identify recurring motivational patterns. The findings reveal eight dominant viewing motives: passing time, companionship, escape, enjoyment, social interaction, relaxation, information acquisition, and excitement. The results indicate that dashcam video consumption reflects a multifaceted media use pattern in which viewers pursue both utilitarian benefits, such as road safety awareness, and emotional gratification. The study confirms the applicability of the Uses and Gratifications Theory to emerging user-generated audiovisual content. Dashcam viewers function as active media users who selectively engage with niche content to satisfy specific psychological and informational needs, highlighting the evolving dynamics of digital media consumption among Generation Z.